Evaluación del comportamiento estructural de una base granular con sustitución parcial del agregado fino por calamina de laminación (2020)
Calamine or rust scale is an important residue of steelmakers, mainly steel mills; This waste represents an environmental and economic problem for the different companies, taking into account that this material can be used by reincorporating it in a productive process. The purpose of this paper is to investigate and evaluate the structural incidence of partial substitution of the fine aggregate of a granular base (BG- 38) with calamine. Two tests were carried out with granular base material supplied by the Solarte-Solarte consortium; a control test with three specimens (without calamine) manufactured with a different level of compaction as stipulated in the standard for conducting the CBR test (5 layers of compaction with 10, 25 and 56 strokes); and thesecond with three specimens replacing 35.53% of the fine material with calamine; also with different compaction energies, these molds were submerged and finally failed with the California Bearing Ratio (C.B.R.) test; obtaining the following results: the control test yielded a unit weight of 20,804 kN / m3 at 95% of the CBR while the calamine test gave a value of 19,859 kN / m3.